The ASEAN economic community : a work in progress - Institute of Southeast Asian Studies; Basu Das, Sanchita; Menon, Jayant; Severino, Rodolfo C. (Singapore : Institute of Southeast Asian Studies, 2013)
This is an important and timely volume: important because ASEAN is an increasingly significant and influential regional and global actor; and timely because, as the 2015 ASEAN Economic Community target approaches, what is needed is a sympathetic yet arms-length survey of the issues and challenges.
Cover, Title,The ASEAN economic community : a work in progress--Preface, Introduction, TOC,Contents--References, Appendix, Index,Index.